2016
DOI: 10.1093/jrr/rrw103
|View full text |Cite
|
Sign up to set email alerts
|

A robust measurement point for dose verification in delivery quality assurance for a robotic radiosurgery system

Abstract: In this CyberKnife® dose verification study, we investigated the effectiveness of the novel potential error (PE) concept when applied to the determination of a robust measurement point for targeting errors. PE was calculated by dividing the differences between the maximum increases and decreases in dose distributions by the original distribution after obtaining the former by shifting the source-to-axis and off-axis distances of each beam by ±1.0 mm. Thus, PE values and measurement point dose heterogeneity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…We confirmed that there were no steep dose gradients in the collecting volumes of the chambers in the different collimator types. However, a robust measurement point suggested by Kurosu et al30 may have some effect on the results of absolute dose verification. The maximum collimator sizes of the fixed collimators were smaller than that of the other collimators.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that there were no steep dose gradients in the collecting volumes of the chambers in the different collimator types. However, a robust measurement point suggested by Kurosu et al30 may have some effect on the results of absolute dose verification. The maximum collimator sizes of the fixed collimators were smaller than that of the other collimators.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity corrections were considered only for the primary beam attenuation by using the equivalent path length for calculation of TPR. Dose calculation accuracy of the ShioRIS software has been reported elsewhere [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The dose distribution of each BED 2 in the liver was exported using the DICOM-RT image fusion software (ShioRIS TM 2.0, Osaka, Japan). 29 Additionally, we analyzed the relationship between the mean BED 2 values for the liver and the planning target volume (PTV), as well as those between the expected hepatic dysfunctional volume and the PTV in order to estimate the residual volume after radiotherapy. We defined the potential liver dysfunction volume as a liver volume that received a BED 2 of 50 Gy or greater when cirrhotic, or received 75 Gy or greater when normal.…”
Section: Methodsmentioning
confidence: 99%